EFFECTIVENESS OF DECISIONS IN ABSENTIA IN RECOVERY OF ASSETS FROM CRIMINAL ACTS OF CORRUPTION: A LEGAL REVIEW OF ARTICLE 38 OF THE LAW ON ERADICATION OF CRIMINAL ACTS OF CORRUPTION - Faiz Aulia Rahman; Bayu Giri Atmojo; Slamet Tri Wahyudi (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study examines the effectiveness of in absentia judgments in the recovery of assets from corruption crimes based on Article 38 of the Law on the Eradication of Corruption Crimes. The background of this study is based on the phenomenon of many corruption defendants who are absent from trial, so that the judicial process continues through the in absentia mechanism. However, the effectiveness of such judgments in supporting the recovery of state financial losses remains a problem, especially in the aspects of execution and the return of assets resulting from corruption crimes. This study uses a normative legal method (normative juridical) with a statutory approach and a conceptual approach. The results of the study indicate that normatively, Article 38 of the Anti-Corruption Law provides a valid legal basis for courts to render judgments without the presence of the defendant. However, the effectiveness of such judgments in asset recovery is still not optimal because there are obstacles such as difficulties in tracing assets, transfer of asset ownership, limited coordination among law enforcement institutions, and weak asset tracing mechanisms. In addition, there are also juridical obstacles in the form of the lack of comprehensive technical regulations regarding the execution of assets in in absentia cases. Therefore, strengthening regulations and increasing synergy among law enforcement officers are required so that the objective of recovering state losses can be achieved effectively.